Relating a Conceptual Overview of Vaccines Utilization for the Prevention of Rotavirus in Children - Garba, Salisu; Dikko, Malami; Bala, Barga Isiyaka; Aliyu, Abdullahi; Sarkingobir, Yusuf (Darul Yasin Al Sys, 2023)
Rotavirus infection is an emphatic health concern that when left unabated elicits hospitalizations, and deaths of many children due to diarrhea, even in developed countries; let one in poor settings. Likewise, the virus can affect older youngsters and adults resulting in mild infection. The consequences of the rotavirus could not be unconnected with the levels of poor prevention ploys put in place, including the inability of the body of children to counteract the rotavirus with a substantial immunity due to earlier invasion. Thus, it is important to seek for vaccines, because vaccination use in disease prevention is becoming a forefront efficient and easiest way nowadays. This paper brings a conceptual overview of vaccines utilization for the prevention of rotavirus infection in children under the following headings: Introduction, rotavirus vaccines, replicating vaccines, non-replicating vaccines, subunit vaccines, virus like particles, encapsulation, rotavirus vaccination, and conclusion.